Improving the Tradition of Memorizing the Qur'an through the Talaqqi Tadabur Method - Siti Chodijah; Juni Ratnasari (PALAPA, 2025)
This study is motivated by the limited research on effective methods for Qur'an memorization among elderly populations, despite its significant impact on spiritual growth and community engagement. The aim is to analyze the effectiveness of the Talaqqi Tadabur method in enhancing Qur'an memorization among elderly individuals. The research adopts a qualitative design, with a purposive sample of participants aged 50 and above recruited at Masjid Al-Amanah. Data were collected through observation, interviews, and documentation of learning activities, and analyzed using thematic analysis. The findings reveal that the Talaqqi Tadabur method, which combines direct recitation with meaning exploration, significantly improves memorization outcomes and enhances participants’ understanding and engagement with the Qur'an, in alignment with principles of active learning and cognitive support for older adults. The study concludes that the Talaqqi Tadabur method is a culturally and pedagogically relevant approach for Qur'an memorization programs targeting elderly learners. The implications include practical recommendations for religious educators and community leaders to adopt this method, as well as opportunities for future research on integrating technology to support and expand access to this learning model. Keywords: Talaqqi Tadabur; Qur'an Memorization; Elderly Learning; Qualitative Research